Cosmetic formulation : principles and practice - Benson, Heather A. E. (CRC Press, 2019)
Cosmetics are the most widely applied products to the skin and include creams, lotions, gels and sprays. Their formulation, design and manufacturing ranges from large cosmetic houses to small private companies. This book covers the current science in the formulations of cosmetics applied to the skin. It includes basic formulation, skin science, advanced formulation, and cosmetic product development, including both descriptive and mechanistic content with an emphasis on practical aspects. Key Features: Covers cosmetic products/formulation from theory to practice Includes case studies to illustrate real-life formulation development and problem solving Offers a practical, user-friendly approach, relying on the work of recognized experts in the field Provides insights into the future directions in cosmetic product development Presents basic formulation, skin science, advanced formulation and cosmetic product development- Resumé vydavatel
Keywords: kosmetické přípravky; kosmetický průmysl; cosmetics; cosmetics industry; elektronické knihy; kolektivní monografie; electronic books; collective monographs